DECONSTRUCTION OF TAX AMNESTY IN BASED ON PANCASILA VALUES: THE CASE OF INDONESIA - Darmayasa, I Nyoman; Sudarma, I Made; Achsin, H.M.; Mulawarman, Aji Dedi (Accounting Department,, 2017)
The main objective of this study is to deconstruct tax amnesty based on Indonesia’s Principles (Pancasila) values. A post-modern paradigm is used to deconstruct current tax amnesty. The methodology used in this research is a combination of Derrida’s deconstruction and Latif’s thought on historicity, rationality, and actuality. The results show that the initial design of tax amnesty is repatriation, which is inferior in the development of taxpayers’ character. Materiality, selfinterest, and measurement object are tax amnesty logos. Religiosity, honesty, civility, and mutual cooperation are used in a reverse hierarchy of the before mentioned tax amnesty logos. The result of deconstruction is tax amnesty based on Pancasila in order to construct social justice.Tax amnesty is a current issue; however, only a limited number of research was dedicated on the philosophy of tax amnesty law. The research offers new meaning to tax amnesty based on Pancasila values which may encourage voluntary tax compliance.